A study on determinant towards saving behavior in Malaysia / Nur Syahirah Saifuddin and Nur Diana Jamaludin - Saifuddin, Nur Syahirah; Jamaludin, Nur Diana (Faculty of Business and Management, 2016)
This project paper entitled “The Determinant of Saving Behaviours in Malaysia” was conducted from February 2016 until June 2016. The researchers came out with this project paper to investigate the determinant of saving behavior in Malaysia. The dependent variable of the study is saving while independent variables are interest rate, inflation rate, household consumption and income level. The study was conducted in Malaysia and used 34 years period of data. This study used time series data and also applied Multiple Linear Regression method in order to study the existence of relationship between those variables. The result of this study found that interest rate, household consumption and income level has positive significant relationship with saving while inflation rate do not have significant relationship with saving.